Relationship between stress and coping strategies among undergraduate students in Lagos State, Nigeria - Abdul Ghani, Mohamad Salleh; Obiora, Emeka Chike; Daud, Mohd Najmi (Faculty of Human Ecology, UPM, 2024)
This study investigates the impact of stress and coping strategies on academic performance among undergraduate students at Lagos State University in Nigeria, addressing a key gap in understanding how stress levels and coping mechanisms vary across demographic factors such as age, gender, and academic level. Given the increasing pressures faced by Nigerian students due to socio-economic instability, lack of institutional support, and academic demands, this research aims to clarify the relationships between stress, coping strategies, and academic performance, with a specific focus on identifying stress as the primary dependent variable. A cross-sectional survey design was used, and data were collected from 164 students in the Psychology Department. Participants completed the Perceived Stress Scale (PSS), Brief COPE Scale, and Academic Achievement Scale (AAS). The study sought to determine whether age, gender, and academic level significantly influence stress levels, to assess the role of academic performance in perceived stress, and to analyze the types of coping strategies used by students, including any gender-based differences. Results showed no significant associations between stress levels and demographic factors, suggesting that age, gender, and academic level do not meaningfully predict stress among Nigerian undergraduates. Additionally, academic performance was not significantly associated with stress, challenging the assumption that higher academic success reduces stress. The regression analysis revealed that only the coping strategies of Instrumental Support and Planning had weak predictive power in reducing stress. The lack of significant gender differences in coping strategy selection indicates similar coping approaches among male and female students. These findings suggest a need for interventions focusing on enhancing adaptive coping skills, such as Planning and Instrumental Support, which may help students manage stress more effectively. Further research is recommended to explore additional stressors unique to Nigerian higher education.